2017
DOI: 10.24218/jod.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline-niosomes versus Tetracycline Hydrochloride-niosomes: How to Modulate Encapsulation and Percutaneous Permeation Properties

Abstract: Nowdays, the design of the optimalniosomal formulation may ensure the best performance in terms of physico-chemical properties and drug skin permeation. Our study want to propose the loading of Tetracycline or Tetracycline hydrocholoride drugs as strategy to modulate niosomes properties, with particular emphasis on encapsulation and percutaneous permeation behavior. Niosomes were prepared from mixtures of nonionic commercial surfactants with different final value of hydrophilelipophile balance (HLB). Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Surfactants with high HLB values are not capable of forming vesicle because of the high hydrophilicity of their molecules, but Spans and Tweens are suitable non-ionic surfactants for noisomes preparation. 66 One of the mechanisms responsible for skin penetration enhancement of niosomes is a reduction in trans-epidermal water loss (TEWL) and the other is fusion or adsorption of the vesicular drug delivery systems to the skin surface resulting in a higher concentration gradient and so higher skin penetration. Niosomes could also modify the stratum corneum structure and make it looser and more permeable.…”
Section: Niosomesmentioning
confidence: 99%
“…Surfactants with high HLB values are not capable of forming vesicle because of the high hydrophilicity of their molecules, but Spans and Tweens are suitable non-ionic surfactants for noisomes preparation. 66 One of the mechanisms responsible for skin penetration enhancement of niosomes is a reduction in trans-epidermal water loss (TEWL) and the other is fusion or adsorption of the vesicular drug delivery systems to the skin surface resulting in a higher concentration gradient and so higher skin penetration. Niosomes could also modify the stratum corneum structure and make it looser and more permeable.…”
Section: Niosomesmentioning
confidence: 99%
“…Thymol was successfully incorporated into the niosome with 81% EE, which was a suitable encapsulation rate compared to that reported in the other studies [ 34 - 35 ] . Sohrabi et al [ 35 ] reported 73% efficiency for drug entrapment in niosomal carrier for moxifloxacin as a antimicrobial agent.…”
Section: Resultsmentioning
confidence: 84%
“…Nonionic surfactants are safer, fairly non-toxic and biocompatible with the host, and can act as a thickening agent in TDD. Surfactants that exhibit increased HLB values are not capable to form a vesicle due to the advanced hydrophilicity of their particles, however, Tweens and Spans are ideal non-ionic surfactants for the preparation of noisome ( Tavano et al, 2017 ). One of the processes for enhanced permeation of niosomes through the skin is the elimination of trans-epidermal water loss (TEWL) while the alternate mechanism is the adsorption or fusion of the vesicles with skin lipids.…”
Section: Nanocarriers For Transdermal Drug Deliverymentioning
confidence: 99%